Women's Caregiving Experience of Older Persons Living With Alzheimer Disease and Related Dementias and Multiple Chronic Conditions: Using Wuest's Theory - Shelley Peacock RN, PhD; Melanie Bayly PhD; Wendy Duggleby RN, PhD; Jenny Ploeg RN, PhD; Lori Pollard RN, MN; Jennifer Swindle PhD; Heun Jung Lee; Allison Williams PhD; Maureen Markle-Reid RN, PhD; Carrie McAiney RN, PhD (SAGE Publishing, 2020)
Introduction Care of persons living with chronic conditions rests heavily on women within the context of the family. Research demonstrates that women experience more caregiving strain compared to men, yet less is known about the differences in experiences between women carers: namely, wives and daughters. Objective The purpose of this study was to examine and compare the experiences of wife and daughter carers of older adults living with Alzheimer disease and related dementias, plus at least two other chronic conditions. Methods Using qualitative description with Wuest's feminist caring theory of precarious ordering as an analytic framework, interview transcripts of women carer participants who were from the control group of a larger multi-site mixed methods study evaluating the web-based intervention My Tools 4 Care were analyzed. Findings Both wives and daughters experienced daily struggles, altered prospects, and ambivalent feelings around their caring role. Negotiating the role of professional carer was an important part of balancing caring demands and anticipating the future, and women took an active role in trying to harness caring resources. Findings indicated wives and daughters were generally similar in how they described their caregiving, although daughters reported more shared caring and decision-making, and needed to balance paid employment with caregiving. Conclusion Wives and daughters face similar challenges caring for persons with a dementia and multiple chronic conditions, and actively engage in strategies to manage caring demands. The findings illuminate the importance of accessible, appropriate support from professional carers/health care providers, and suggest that assistance navigating such supports would benefit women carers.